فقه النوازل بين الحقل الديني و التوثيق لبناء المعرفة التاريخية نازلة اليهود في توات للمغيلي أنمودجا - فاطمة الزهراء بروقي (My University, 2023)
Summary : With the development of the different historical knowledge and the necessity for alternative documentary sources ,the researchers have mainly adopted it as an Islamic heritage . Thus, these fatawas and Fiqh issues were mainly regarded as an essential source in writing the Arab Islamic, cultural, social and economic history. Hence, the researchers focused mainly on studying it in order to clarify important things about the history of such societies . In this context, The Tawat region experienced an incident movement which played the main role in describing the living situations of the people of Tawat in addition to their political, economic, social and cultural conditions. The Jewish incident in Tawat according to El Mughili helped us to have an almost complete vision about this society during 29/15 AD century. This incident; including the problems of life struggles in its religious aspect. However, we managed to invest it as possible as we can for the sake of studying the economic, social, cultural and political history of the region. ----------------------------------------------------- المخمص: مع تطكر حقكؿ المعرفة التاريخية، ك ازدياد الحاجة لكثائؽ مصدرية بديمة، لجأ الباحثكف الى التماسيا حيث يحفؿ بيما الت ارث اإلسالمي، فشكمت بذلؾ الفتاكم كالنكازؿ الفقيية مصد انر أساسيان في كتابة التاريخ الثقافي اىتماـ الباحثيف عمى د ارستيا كتحقيقيا مف أجؿ كاالجتماعي ك االقتصادم العربي اإلسالمي، كمف ىنا انص ّب استجالء صفحات ىامة مف تاريخ ىذه المجتمعات. كفي ىذا السياؽ عرفت منطقة تكات حركة نكازلية كصفت لنا الكاقع المعيش لسكاف تكات كأكضاعيـ السياسية كاالقتصادية كاالجتماعية كالثقافية، فأعطت لنا نازلة الييكد في تكات لممغيمي صكرة شبو متكاممة عف المجتمع التكاتي خالؿ القرف 9ىػ15/ـ. إ ّف ىذه النازلة بما تضمنتو مف إشكاالت الحياة في جانبيا الديني إالّ أننا تم ّكنا مف استثمارىا قدر المستطاع في إطار د ارسة التاريخ االقتصادم كاالجتماعي كالثقافي كالسياسي لممنطقة. ----------------------------------------------------------------------------------- Résumé Avec le développement du savoir historique,et la croissance du besoin de documents et de sources remplaçants,le chercheurs ont y recouru ,puisque le patrimoine musulman y est riche.cela a produit des fetwas nazla et de doctrine qui sont fondamentaux dans l' écriture de l, histoire culturelle, sociale,et économique .arabo islamique Et dans ce contexte la région a connu un mouvement nawazel qui a décrit la réalité de la vie des habitants de twat et leurs conditions politiques, économiques, sociales et culturelles. cela a donné cette nazla juif à twat comme une image presque complète sur la société twati pendant le siècle 9 hijri 15 c. cette nazla comporte les problèmes de la vie et aussi du côté de la religion et on apu l, investir comme l,on peut dans le domaine de l, étude de l, histoire économique, sociale culturelle et politique de la région.